SOCIODEMOGRAPHIC, HEALTH, AND PSYCHOSOCIAL CHARACTERISTICS RELATED TO INCONSISTENCIES IN PAIN MEASUREMENTS. (11th November 2018) - Sardina, A; Gamaldo, A A; Andel, R; Zonderman, A B; Evans, M K
Abstract: This cross-sectional study, which included Black and White adults (n=887; aged 30–64) from the Healthy Aging in Neighborhoods of Diversity across the Life Span (HANDLS) study, explored whether sociodemographic, health, and psychosocial predictors were associated with inconsistent subjective and objective pain measurements (pain upon passive range of motion) in the hands, neck, and low back. Findings indicated that those who reported the combination of a history of depressive symptoms and being below poverty status were nearly 3 times more likely to demonstrate inconsistent neck pain measurements (β=-.28, p<.001, OR=3.0, 95% CI=1.66, 5.43). Additionally, individuals with a history of depressive symptoms who reported neighborhood quality as "poor" to "fair" were 3.3 times more likely to demonstrate inconsistent low back pain measurements (β=.30, p<.001, OR=3.32, 95% CI=2.10, 5.24). These findings suggest the need for pain management strategies tailored to address not only unique individual characteristics, but also contextual factors across diverse groups.